Analysis of Inheritance Division Based on Deeds Made Before Notary in Perspective of Sadd al-Dzari’ah (Study at Notary Office of Bengkulu City) - Rizfitriani Alamsyah; Toha Andiko (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This research aims to explain: 1) How is the distribution of inheritance made by the heirs based on the deed made before the notary perspective of Sadd Al-Dzari’ah?, 2) What is the position of the inheritance distribution deed made before the notary perspective of Sadd Al-Dzari’ah?. This type of research is library research. Data collection techniques using the Document Method. The conclusion states that, 1) The heirs in dividing the inheritance do not use the Islamic inheritance system but are divided in a family manner using each party discussing each other looking for a way out of the inheritance problem being faced. 2) The implementation of the inheritance distribution in a family is not intended to avoid furudhul muqaddarah (the part set out in the text), but is nothing but for the benefit of all heirs and avoid kemudharatan. To prevent this kemudharatan, then made the Deed of Inheritance before the notary public. So in the perspective of sadd al-dzari’ah, the position of making the deed of distribution of legal inheritance is sunnah